Intervenciones del Desarrollo Organizacional para lograr una buena gestión de recursos humanos en la Municipalidad Provincial de Virú - Correa Valdez, Karen América (2012)
This study investigated Interventions Organizational Development and Human Resource Management in workers of the Provincial Municipality of Viru. The problem posed in this study is Which of the Organizational Development interventions is optimal for good Human Resource Management? with the hypothesis that the Human Process Interventions is optimal for good Human Resources Management. The Provincial Municipality of Viru is formed by 220 workers and for purposes of this study we have worked with a sample of 141workers. Were used as data collection techniques to the survey and a pilot program of six days (which served to manipulate variables and measure results). The results obtained are used to demonstrate that Organizational Development Interventions are important for the municipality. In conclusion, after applying the pilot was obtained that the Human Process Interventions are optimal to be implemented in the municipality, corroborating what was initially proposed in the present study. We recommend the implementation of a program of Human Process Interventions to achieve good Human Resource Management.